HUBUNGAN KEPEMIMPINAN DENGAN KINERJA TENAGA KESEHATAN DI PUSKESMAS TAMALANREA JAYA KOTA MAKASSAR - St. Risky Muthmainnah Ansar; Amran Razak; Suci Rahmadani (Homes Journal = Hospital Management Studies Journal, 2023)
Performance can be defined as the evaluation of employees' accomplishments in relation to pre-established work standards. One of the factors that affect performance is the leadership factor of a leader to be able to communicate and influence his subordinates so that they can work to achieve organizational goals. Purpose: This study aims to examine the impact of different leadership factors, such as leader-member relationships, task structure, and the leader's position power, on the performance of healthcare staff at the Tamalanrea Jaya Health Center in Makassar City. Methods: The study conducted between January and April 2023 at Tamalanrea Jaya Health Center involved a population of 37 health workers who were selected using the total sampling technique. The research method employed was a cross-sectional design with a quantitative approach. The data analysis techniques used were univariate and bivariate, and the tests applied were the Fisher exact test and contingency coefficient test. Results: The study's findings revealed that the performance of healthcare professionals at Tamalanrea Jaya Health Center was associated with three factors: leader-member relationship (p=0.001), task structure (p=0.012), and the leader's power position (p=0.005). Conclusion: The performance of healthcare workers at the Tamalanrea Jaya Health Center in Makassar City is correlated with leader-member relations, task structure, and the power of the leader's position. It is recommended for leaders to improve supervision and evaluation related to discipline and timeliness of entering employee working hours